The role of heat shock proteins in HIV-1 pathogenesis: a systematic review investigating HSPs-HIV-1 correlations and interactions - Chyntia Tresna Nastiti; Noer Halimatus Syakdiyah; R.M. Firzha Hawari; Youdiil Ophinni; Ni Luh Ayu Megasari (PeerJ, 2024)
Background The human immunodeficiency virus (HIV) pandemic is a global health emergency. Studies suggest a connection between heat shock proteins (HSPs) and HIV-1 infection pathogenesis. This systematic review aims to summarize HSPs’ role in HIV-1 infection pathogenesis. Materials and Methods A systematic literature search was undertaken across the National Library of Medicine (MEDLINE-PubMed), Science Direct, Web of Science, Scopus, SpringerLink, Sage, ProQuest, and Google Scholar databases, using related keywords to synthesize the HSPs’ role in HIV-1 infection pathogenesis. This literature review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the protocol was registered in the Open Science Framework (OSF) database under DOI 10.17605/OSF.IO/VK3DJ. Results A database search revealed 3,332 articles, with 14 in vitro studies analysing the interaction between HSPs and HIV-1 across different cell types. HSPs are involved in HIV-1 infection through direct interactions and indirect responses to cellular stress, including HSP40, HSP70, HSPBP1, and HSP90. The study explores HSP interactions at various stages of the viral life cycle, including entry, uncoating, replication, transmission, and latency reactivation. Conclusion HSPs are crucial for the HIV lifecycle and immune response, offering the potential for new therapeutic strategies. Further research is needed to understand the clinical significance and target potential.